The Effect of Formula Milk Consumption on Nutritional Status Toddlers Aged in the Work Area of UPTD Puskemas Yaro Village Jaya Mukti Nabire District - Orpa Irianti Bonsapia; Nur Al-faida; Gandhi Pratama (International Journal of Public Health, 2024)
A child's life is very important, and parental attention is also important. Babies need to get nutrition from food every day in the right amount and good quality every day. One way to optimize child growth and development is by giving formula milk. Objective: To determine the effect of formula milk consumption on the nutritional status of toddlers in the Working Area of ​​the Yaro Health Center UPTD, Jaya Mukti Village, Nabire Regency. Method: This type of research is quantitative research using observational analysis research design and cross-sectional study design. The population in the study was 65 toddlers and the selected sample consisted of 65 toddlers using total sampling. The research instruments included questionnaires, anthropometric measuring instruments (digital scales and length boards), stationery and documentation tools. The analysis used the Release Statistical Program For Science (SPSS) type 16.0 application. Results: The study showed that the BB/TB index p-value was 0.00 (<0.05), the BB/A index p-value was 0.00 (<0.05) and the TB/A index p-value was 0.00 (<0.05). Conclusion: There is an effect of giving formula milk on the nutritional status of toddlers based on anthropometric measurements using the Body Weight/Height (BW/TB), Body Weight/Age (BW/U) and Height/Age (BH/U) indices. Suggestion: For parents to pay attention to the appropriateness of the dosage, frequency of giving and sanitation of serving formula milk to achieve optimal nutritional status.